Zwrot ku codzienności w badaniach nad religią - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2023)
Article Turning to everyday life in religion research postulates the need to use a new methodology in the analysis of religion. It was proposed by the French cultural anthropologist Michel de Certeau. It is creatively developed by such anthropologists as Nancy T. Ammerman, Hugh Turpin and Catherine Wanner. In this context, the author points to the limitations of traditional methods of studying Polish religiosity. He also proposes his own way of overcoming these limitations. It is listening to the voice of lay Catholics.